Linking statistical and hydrodynamic modeling for compound flood hazard assessment in tidal channels and estuaries - Moftakhari, Hamed; Schubert, Jochen E.; AghaKouchak, Amir; Matthew, Richard A.; Sanders, Brett F. (Advances in water resources, 2019)
•Compound flood hazard levels computed for tidal channels or estuaries.•Bivariate statistical and hydrodynamic modeling is linked.•Spatially distributed flood hazard levels computed for return period T.•Method accounts for statistical and physical compounding effects. A method to link bivariate statistical analysis and hydrodynamic modeling for flood hazard estimation in tidal channels and estuaries is presented and discussed for the general case where flood hazards are linked to upstream riverine discharge Q and downstream ocean level, H. Using a bivariate approach, there are many possible combinations of Q and H that jointly reflect a specific return period, T, raising questions about the best choice as boundary forcing in a hydrodynamic model. We show, first of all, how possible Q and H values depend on whether the definition of T corresponds to the probability of exceedance of “H OR Q” or “H AND Q”. We also show that flood hazards defined by “OR” return periods are more conservative than “AND” return periods. Finally, we introduce a new composite water surface profile to represent the spatially distributed hazard for return period T. The composite profile synthesizes hydrodynamic model results from the “AND” hazard scenario and two scenarios based on traditional univariate analysis, a “Marginal Q” scenario and a “Marginal H” scenario.